2002
DOI: 10.1021/ar000204k
|View full text |Cite
|
Sign up to set email alerts
|

The Beginnings of Vitreous Materials in the Near East and Egypt

Abstract: In the Near East and Egypt, vitreous materials in the form of glazed stones and faience were first produced from about the 4th millennium B.C. Subsequently, the period around 1500 BC saw major developments in the range of vitreous materials with the production of glass vessels and glazed clay objects and an extension in the range of colorants used. This paper first describes how the examination of artifacts has been used to reconstruct the processes involved in the production of these different vitreous materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
13

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 12 publications
0
22
0
13
Order By: Relevance
“…Glass objects in the form of small beads and amulets are occasionally found since the late third millennium BC; however, a regular production of glass vessels does not seem to occur before the Late Bronze Age, around 1500 BC in Mesopotamia and in Egypt (Peltenburg, 1971;Tite et al, 2002). Early glass was found to be silica-sodalime in composition, with relatively high levels of potassium and magnesium; these elements were usually introduced through two main ingredients, namely sodic ash derived from desert plants, on the one hand, and crushed quartz pebbles or a relatively calciumfree sand, on the other (Vandiver, 1983;Brill, 1999, vol 1, pp.…”
Section: Introductionmentioning
confidence: 99%
“…Glass objects in the form of small beads and amulets are occasionally found since the late third millennium BC; however, a regular production of glass vessels does not seem to occur before the Late Bronze Age, around 1500 BC in Mesopotamia and in Egypt (Peltenburg, 1971;Tite et al, 2002). Early glass was found to be silica-sodalime in composition, with relatively high levels of potassium and magnesium; these elements were usually introduced through two main ingredients, namely sodic ash derived from desert plants, on the one hand, and crushed quartz pebbles or a relatively calciumfree sand, on the other (Vandiver, 1983;Brill, 1999, vol 1, pp.…”
Section: Introductionmentioning
confidence: 99%
“…The early production of glass was based on silica as the network former, soda as the alkali flux, and lime and magnesium as stabilizers. Tite et al [32] have suggested for such mixtures a furnace temperature in the range of 1100e1200 C, which is well beyond the required range for pottery production. Thus temperature alone is unlikely to definitively differentiate between various pyrotechnological practices.…”
Section: Introductionmentioning
confidence: 99%
“…3, the potash content of cobalt-blue glasses is significantly lower than that of the copper-blue or glasses of other colours. This behaviour has been observed in Egyptian glasses and led Tite et al (2002) to propose that plant ashes of different composition (i.e. lower in potash, higher in magnesium and lime) were used for the production of cobalt-blue glasses.…”
Section: Soda Fluxmentioning
confidence: 86%
“…The association of copper to tin, when observed in glass XRF data, indicates the use of bronze or bronze scraps as colourants (Tite et al, 2002) but there are not any significant amounts of tin in the Pylos beads (the detection limit for Sn is 150 ppm, see Table 2). The source of the copper colourant of the Pylos glasses could have been either corroded copper metal or a copper mineral, such as malachite or azurite (Tite et al, 2002). The cobalt may be of European or Middle Eastern origin.…”
Section: Colourants and Opacifiersmentioning
confidence: 96%
See 1 more Smart Citation